ON A RATE OF CONVERGENCE IN THE $GI|G|1|∞$ MODEL - Grigoryan, T. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
In the present paper one more estimation on a rate of convergence of actual waiting time to its stationary value in the $GI|G|1|∞$ model is obtained. It leads to a similar estimation for total empty time of a server when the traffic intensity of the model is more than one.
Keywords: rate of convergence; actual waiting time; traffic; total empty time